Poor sleep quality has an adverse effect on childhood asthma control and lung function measures. Issue 8 (23rd June 2017) - Sheen, Youn Ho; Choi, Sun Hee; Jang, Sun Jung; Baek, Ji Hyeon; Jee, Hye Mi; Kim, Mi Ae; Chae, Kyu Young; Han, Man Yong
Abstract: Background: It is unclear as to whether sleep respiratory breathing disorder (SRBD) is a risk factor for uncontrolled asthma in children. The aim of this study was therefore to investigate whether SRBD may have an adverse effect on childhood asthma control and lung function measures. Methods: This was a cross‐sectional study of 220 children with well‐controlled ( n = 108), partly controlled ( n = 92), and uncontrolled asthma ( n = 20) according to the Global Initiative for Asthma guideline. SRBD was assessed using the Pediatric Sleep Questionnaire (PSQ). The association of SRBD with partly controlled/uncontrolled asthma was investigated on multivariate logistic regression analysis. Results: Of 220 children with asthma, 43 (19.6%) had SRBD: well‐controlled, 16.7% (18/108); partly controlled, 21.7% (20/92); and uncontrolled, 25.0% (5/20; P = 0.54). There was a significant difference in forced expiratory volume in 1 s/forced vital capacity (FEV1 /FVC; P = 0.007) and childhood asthma control test (C‐ACT) score ( P < 0.001) according to asthma control status, but not in PSQ score ( P = 0.18). Children with obstructive sleep apnea (PSQ >0.33) had a lower C‐ACT score compared with controls (PSQ ≤0.33; 19.6 ± 5.1 vs 22.0 ± 4.2, P = 0.002). PSQ score was negatively correlated with FEV1 /FVC ( r = −0.16, P = 0.02). On multivariate logistic regression analysis, high PSQ score increased the odds of having partly controlled/uncontrolled asthma by 9.12 (95% CI: 1.04–79.72, P = 0.046) after adjusting for confounding factors. Conclusion: SRBD is an independent risk factor for partly controlled/uncontrolled asthma and has an adverse effect on lung function measures in children. Further research is warranted to determine whether the improvement of sleep quality may also enhance level of asthma control and lung function in children.